2013
DOI: 10.1186/1476-069x-12-74
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of child morbidity in regions of Ostrava, Czech Republic, with different degrees of pollution: a retrospective cohort study

Abstract: BackgroundTo confirm or refute the hypothesis that the morbidity of children (since birth to age 5) born and living in the heavily polluted (PM10, benzo[a]pyrene) eastern part of Ostrava, Czech Republic, was higher than the morbidity of children living in other parts of the city.MethodsTen pediatricians in 5 districts of Ostrava abstracted the medical records of 1878 children born in 2001–2004 to list all illnesses of each child in ICD-10 codes. The children were divided into four groups according to their res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…The association between particle number and PM2.5 concentrations and daily hospital admissions due to cardiovascular and respiratory diseases was reported for Prague [165]. A long-term study of the health impacts of air pollution on children in heavily polluted parts of the CR revealed that air pollution significantly affected children's health and resulted in increased respiratory morbidity [166,167]. Due to long-term monitoring results, the Moravian-Silesian region/Ostrava region is recognised not only as a Czech hotspot for PM and BaP, but also truly as a European hotspot [22,106].…”
Section: Aerosolmentioning
confidence: 99%
“…The association between particle number and PM2.5 concentrations and daily hospital admissions due to cardiovascular and respiratory diseases was reported for Prague [165]. A long-term study of the health impacts of air pollution on children in heavily polluted parts of the CR revealed that air pollution significantly affected children's health and resulted in increased respiratory morbidity [166,167]. Due to long-term monitoring results, the Moravian-Silesian region/Ostrava region is recognised not only as a Czech hotspot for PM and BaP, but also truly as a European hotspot [22,106].…”
Section: Aerosolmentioning
confidence: 99%
“…Comparing the detailed age-specific morbidity of 1655 children born and living in the district of Ostrava Radvanice-Bartovice (R&B) vs. children in other parts of Ostrava, a significantly higher incidence of acute illness was observed. Children from R&B experienced a higher incidence of acute respiratory disease in the first year of life ( Figure 2) and a higher prevalence of asthma bronchiale (37.1%, N = 170) compared to other parts of Ostrava (10.2-13.2%, N = 1287) [27]. From birth until the age of 5 years, the incidences of pneumonia, tonsillitis, viral infections, and intestinal infectious diseases were also several times higher in children living in the district of Ostrava Radvanice-Bartovice.…”
Section: Child Morbidity In the City Of Ostravamentioning
confidence: 99%
“…The morbidity in the city of Ostrava was studied in 10 pediatric districts in children born from 2001 to 2004 up to 5 years of age (N = 1888) [27]. The pediatricians abstracted medical records in ICD-10 codes.…”
Section: Child Morbidity In the City Of Ostravamentioning
confidence: 99%
“…Other risk factors of allergic asthma include family histories of atopic diseases and cigarette smoke exposures. Children with early-onset wheezing symptoms have greater susceptibility to frequent infections and eczema compared with those children with later onset asthma (4,16). Among the sensitized infants/toddler, respiratory viral infections (e.g.…”
Section: Allergic Asthmamentioning
confidence: 99%